Citadels of Freedom: Lina Bo Bardi's SESC Pompéia Factory Leisure Centre and Teatro Oficina, São Paulo. (November 2013) - Sara, Rachel; Mosley, Jonathan; Sara, Rachel
Abstract Transgression is by implication transdisciplinary, slipping beyond accepted boundaries. Rachel Sara describes how Brazilian architect Lina Bo Bardi designed her buildings in a state of 'incompleteness', so as to be ready for a collaborative occupancy in 'recognition that the users' experiences construct the architecture as much as the architect herself'.